A joint control model for connected vehicle platoon and arterial signal coordination. Issue 1 (2nd January 2020) - Wang, Pangwei; Jiang, Yilun; Xiao, Lin; Zhao, Yi; Li, Yinghong
Abstract: The emerging advanced intelligent transportation systems, such as connected vehicles (CV) and cooperative vehicle-to-infrastructure system (CVIS), attract much research attentions nowadays. Taking the advantages of such systems, first, this article develops a joint control model which optimizing the speeds of the connected vehicles and coordinating signals along an arterial simultaneously. This control model forms connected vehicles into platoons so that the vehicles can pass through intersections together with no stops or the least stop time. At the same time, it optimizes signal timing plans along an arterial to achieve lower signal delay and higher throughput. Finally, the proposed model is tested on a mimic of a real-world road network in simulation. Compared with the MAXBAND model, the results indicate that the joint control model can reduce the stop time and stops of coordinate phase by up to 53.69% and 41.15%. The signalized intersection delay per vehicle is reduced by 13.19%. Meanwhile, the vehicle queue is eliminated by the platoon control and arterial signal coordination. The sensitivity analysis also shows that the signalized intersection delay reduction is proportional to the traffic flow volume.